The use and costs of chiropractic care in the Health Insurance Experiment - Shekelle, Paul G.; Rand eBooks (Santa Monica, CA : RAND, 1994)
In this report, data from the RAND Health Insurance Experiment (HIE) were analyzed to answer significant research questions about chiropractic health services. The HIE was a population-based, randomized controlled trial that tracked the use of medical services and the health status of enrollees over a three- or five-year period. Information was taken directly from the HIE claims form and combined with demographic and health status information collected on the HIE participants at enrollment. Chiropractic users were more likely than nonusers to be white, between the ages of 18 and 50, high school graduates, and married. Cost-sharing decreased annual chiropractic expenditures by about one-half. Chiropractic episodes of care were among the lowest in total cost but were among the highest in outpatient costs.
Prepared within RAND's Health Sciences Program.
Includes bibliographical references (p. 85-89).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: Backache -- Chiropractic treatment; Insurance, Health -- United States; Medical care, Cost of -- United States; Back Pain -- economics -- United States; Chiropractic -- economics -- United States; Community Health Services -- utilization -- United States; Cost Sharing; Insurance, Health -- United States; Electronic books